Obstetric violence against women in the Portuguese context: A qualitative in-depth approach - Aires, E.; Antunes, C.; Magalhães, E.; Ferreira, C. (Violence Against Women, 2025)
Evidence suggests that women worldwide experience mistreatment during institutional childbirth. This qualitative study aimed to explore obstetric violence in Portugal, specifically, its related factors and perceived impact. The inductive thematic analysis of 19 semi-structured interviews with women living in Portugal (22–41 years old), who identified themselves as victims, revealed six central themes: (1) obstetric violence, (2) the impact of obstetric violence, (3) victims’ awareness, (4) coping strategies, and (5) explanatory factors. This study adds relevant evidence on what (experiences), why (explanatory factors), and how (processes and coping strategies) obstetric violence might occur, as well as its psychological, interpersonal, and physical impacts.